The resilience of communities and nature-based livelihoods in northern Finland - Simo Sarkki; Hannu I. Heikkinen (The Geographical Society of Northern Finland, 2012)
Resilience has become a key concept for assessing sustainability in relation to socio-environmental change in the North. This article considers various case studies in northern Finland relating to reindeer herding, forestry and nature conservation to drawupon lessons learned for resilience studies. Mainstream literature on northern resilience focuses on resilience of local livelihoods to only certain kind of disturbances, such as climate change and resource extraction. However, also conservation efforts may threaten specific livelihoods, but there seems to be a gap regarding assessing resilience in terms of conservation efforts. This article aims to fill this gap by examining resilience of forestry and reindeer herding, important northern livelihoods, to increasing conservation efforts. It is also recommended that resilience studies should be cautious regarding the definition of the system when they are assessing its resilience. We introduce a distinction between community resilience and the resilience of livelihoods communities depend upon.